RE-OS ISOTOPIC DATING AND ITS GEOLOGICAL IMPLICATION OF BAIMAZHAI CU-NI SULPHIDE DEPOSIT, YUNNAN PROVINCE, CHINA - Shi G.Y.; Sun X.M.; Wang S.W.; Xiong D.X.; Qu W.J.; Du A.D. (My University, 2006)
Re-Os isotopic age of sulfide ores from Baimazhai Cu-Ni sulphide deposit in Yunnan province was determined by using carius tube decomposing technique, acetone extracted Re and inductively coupled plasma mass spectrometry(ICP-MS). The results show that the Re-Os isochron age is 259 ± 18Ma (MSWD = 0.055), with an initial 187Os/188 Os value of 0.455 ± 0.024 and a corresponding (Os(t) of + 263. The Re/Os ratios of sulfide ores vary from 11.56 to 21.04. The data suggest that ore-forming age of the Baimazhai Cu-Ni deposit was very close to major eruption stage of the Emeishan large igneous provinces (LIPs), and the ore-forming material derived both from the mantle and the crust. The content of crust-derived Os was estimated to be ~30%.
Keywords: BAIMAZHAI CU-NI SULFIDE DEPOSIT; CU-NI SULFIDE ORES; GEOLOGICAL IMPLICATION; ICP-MS; RE-OS ISOTOPIC DATING